Mediation of Successful Reperfusion Effect through Infarct Growth and Cerebral Edema: A Pooled, Patient‐Level Analysis of EXTEND‐IA Trials and SELECT Prospective Cohort. Issue 4 (17th January 2023) - Sarraj, Amrou; Pujara, Deep K.; Churilov, Leonid; Sitton, Clark W.; Ng, Felix; Hassan, Ameer E.; Abraham, Michael G.; Blackburn, Spiros L.; Sharma, Gagan; Yassi, Nawaf; Kleinig, Timothy; Shah, Darshan; et al.
Abstract : Objective: Reperfusion therapy is highly beneficial for ischemic stroke. Reduction in both infarct growth and edema are plausible mediators of clinical benefit with reperfusion. We aimed to quantify these mediators and their interrelationship. Methods: In a pooled, patient‐level analysis of the EXTEND‐IA trials and SELECT study, we used a mediation analysis framework to quantify infarct growth and cerebral edema (midline shift) mediation effect on successful reperfusion (modified Treatment in Cerebral Ischemia ≥ 2b) association with functional outcome (modified Rankin Scale distribution). Furthermore, we evaluated an additional pathway to the original hypothesis, where infarct growth mediated successful reperfusion effect on midline shift. Results: A total 542 of 665 (81.5%) eligible patients achieved successful reperfusion. Baseline clinical and imaging characteristics were largely similar between those achieving successful versus unsuccessful reperfusion. Median infarct growth was 12.3ml (interquartile range [IQR] = 1.8–48.4), and median midline shift was 0mm (IQR = 0–2.2). Of 249 (37%) demonstrating a midline shift of ≥1mm, median shift was 2.75mm (IQR = 1.89–4.21). Successful reperfusion was associated with reductions in both predefined mediators, infarct growth (β = −1.19, 95% confidence interval [CI] = −1.51 to −0.88, p  < 0.001) and midline shift (adjusted odds ratio = 0.36, 95% CI = 0.23–0.57, p  < 0.001). Successful reperfusion association with improved functional outcome (adjusted common odds ratio [acOR] = 2.68, 95% CI = 1.86–3.88, p  < 0.001) became insignificant (acOR = 1.39, 95% CI = 0.95–2.04, p  = 0.094) when infarct growth and midline shift were added to the regression model. Infarct growth and midline shift explained 45% and 34% of successful reperfusion effect, respectively. Analysis considering an alternative hypothesis demonstrated consistent results. Interpretation: In this mediation analysis from a pooled, patient‐level cohort, a significant proportion (~80%) of successful reperfusion effect on functional outcome was mediated through reduction in infarct growth and cerebral edema. Further studies are required to confirm our findings, detect additional mediators to explain successful reperfusion residual effect, and identify novel therapeutic targets to further enhance reperfusion benefits. ANN NEUROL 2023;93:793–804